The Position of Financial and Human Resource Readiness Which One The More Ready for Industry 4.0 Adopting? - Karnawati, Hennidah; Purwihartuti, Koernia; Angestiwi, Tiafahmi; Kristianingsih (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
Cooperatives are born from an agreement between a group of people, are part of a business organization that seeks to obtain profits for all members and owners, so management standards are needed that balance economic and social motives. This motive can be achieved by optimizing the use of Islamic cooperative resources, both financial and human resources. This optimization can be enhanced by the use of technology... Objective: To evaluate the level of readiness of financial and human resources in Sharia Cooperatives in West Java to adopt Industry 4.0. Method: A descriptive survey of 196 sharia cooperative practitioners, interviews with 39 sharia cooperative leaders, and a study of several government regulations on sharia, including several MUI fatwas, were conducted. The data were analyzed descriptively. Result: Empirical evidence shows that financial and human resources have achieved extraordinary results. Surveys show that financial resources are more prepared than human resources (employees) to adopt Industry 4.0.